The behavior of some wheat cultivars in relation to soil phosphorus - Ben, J.R.; Rosa, O.S. (Pesquisa Agropecuaria Brasileira, 2014)
Aiming at to assess the behavior of some wheat cultivars in relation to phosphorus, an experiment was conducted in pots, under screen house conditions. The soil used belong to the Passo Fundo Soil Mapping Unit (Dark Red Dystrophic Latosol), with low phosphorus availability and high content of exchangeable aluminum. Treatments consisted of three doses of phosphorus (0, 30. And 60 ppm P2O5 ) and six cultivars (Toropi, PG 1, BH 1146, CNT 1, IAC 5-Maringá, and Alondra Sib). An experimental design involving randomized blocks with four replications was used. Dry matter weight of both above-ground part and root as well as of phosphorus in the tissue was assessed, and the plants were harvested at flowering stage. Cultivars Toropi and PG 1 - as compared to BH 1146, CNT 1, and IAC 5-Maringá - showed greater capacity to develop in soil with low availability of phosphorus under acid conditions as well as greater use of either native or added phosphorus, indicating flue possible occurrence of genetic variability, among the material assessed, for the factor under study. Data obtained from cultivar Alondra Sid did not allow the assessment of its behavior, in relation to phosphorus, duo to the susceptibility of this cultivar the acidity factors present in the soil.